2022
DOI: 10.1108/rbf-09-2020-0223
|View full text |Cite
|
Sign up to set email alerts
|

The impact of anchoring bias on investment decision-making: evidence from Ghana

Abstract: PurposeThe objective of this paper is to explore how anchoring affects the dynamics of investor decision-making with regard to mutual funds and how this bias differs amongst gender and level of financial knowledge.Design/methodology/approachAn experimental research design was adopted to uncover the relationship between the variables under study; this involved the use of a questionnaire with an embedded experiment. Data obtained from the study were analysed using Pearson's chi-square test and two-way analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…A similar strand holds in the literature 20 that assessed the influence of psychological biases on the investors' performance in the Tehran Stock Exchange and revealed that availability bias, herding, and anchoring are the main influential factors for investors' performance. In addition to this, Laryea and Owusu (2023) 21 reveal that investors were prone to be significantly influenced by the anchoring bias. Das and Panja (2022) 22 also established the positive and significant impact of biases such as overconfidence, self-attribution and market reaction on investors' decision-making.…”
Section: Behavioural Biases and Investment Performancementioning
confidence: 91%
“…A similar strand holds in the literature 20 that assessed the influence of psychological biases on the investors' performance in the Tehran Stock Exchange and revealed that availability bias, herding, and anchoring are the main influential factors for investors' performance. In addition to this, Laryea and Owusu (2023) 21 reveal that investors were prone to be significantly influenced by the anchoring bias. Das and Panja (2022) 22 also established the positive and significant impact of biases such as overconfidence, self-attribution and market reaction on investors' decision-making.…”
Section: Behavioural Biases and Investment Performancementioning
confidence: 91%
“…By looking at a primary value or initial position and changing it until it fits the final decision. According to Owusu (2020), anchoring describes an irrational inclination towards a benchmark figure. This benchmark skews market participants' investment decisions.…”
Section: The Covid-19 Pandemic Does Not Mediate the Relationship Betw...mentioning
confidence: 99%
“…Typically, such bias is developed when an investor pays attention to unjustified information, which causes errors in decision-making (Saravanan & Totawar, 2021). Owusu and Laryea (2022) examine how anchoring affects investor decision-making regarding mutual funds and how this bias varies based on gender and financial literacy. They show that females are more likely to anchor than males.…”
Section: Behavioral Biases and Investment Decision-makingmentioning
confidence: 99%